A pediatric case of ureterolithiasis due to cystinuria accompanied by acute appendicitis; a case report. (October 2022) - Hiraoka, Tomohiro; Kawamura, Mai; Takada, Keisuke; Moriwake, Tadashi
Abstract: Introduction: Acute abdominal pain, a chief complaint frequently seen in the emergency department, can be triggered by a vast range of conditions. Although ureterolithiasis is a less common cause in children, renal colic can be caused by calculi due to hereditary metabolic diseases among patients in those age groups. Presentation of case: We report a 12-year-old girl with abdominal pain who was diagnosed with concurrent acute appendicitis and ureterolithiasis due to cystinuria. Acute appendicitis was successfully treated with cefmetazole, and the calculus was eliminated after adequate fluid loading. Discussion: Synchronous acute appendicitis and ureterolithiasis is reported to be rare. Cystinuria is a hereditary metabolic stone-forming disease, and the first calculi can be detected in childhood. Increasing the solubility of cystine in the urine is required to prevent recurrent stone formation and accompanying complications. Urinalysis, ultrasound, and computed tomography coincidentally demonstrated two different acute pathological processes of ureterolithiasis and appendicitis. Conclusion: Careful physical and laboratory examination can help clinicians find coexisting etiologies of acute abdominal pain. Ureterolithiasis can be seen in children with hereditary disorders such as cystinuria. Early diagnosis of cystinuria and close monitoring may lead to a better long-term outcome. Highlights: Abdominal pain can be caused by coexisting different disease processes. Patients with cystinuria usually experience the first stone formation in childhood. Diagnostic clues: cystine stone, hexagonal crystals, and urinary cystine excretion Treatments include adequate fluid intake, urinary alkalinization, and nutritional therapy. A proper selection of imaging modalities is needed for the assessment and follow-up.